Cooperation in the Classroom: Experimenting with R&D Cooperatives - Michelle Sovinsky Goeree; Jeroen Hinloopen (Tinbergen Institute, 2006)
This paper describes a classroom experiment that illustrates the research and development investment incentives facing firms when technological spillovers are present. The game involves two stages in which student sellers first make investment decisions then production decisions. The classroom game can be used to motivate discussions of research joint ventures, the free-rider problem, collusion, and antitrust policy regarding research and development.
Keywords: C91; L13; L41; 330; classroom games; research and development; research joint ventures; technological spillovers